STRUKTUR KEPEMILIKAN, KEBIJAKAN HUTANG DAN PERTUMBUHAN ASET TERHADAP KEBIJAKAN DIVIDEN - Oktaviatin, Nur Laeli; Wiharno, Herma; Purnama, Dendi (Jurnal Riset Keuangan dan Akuntansi, 2024)
This study aims to analyze the effect of managerial ownership, institutional ownership, public ownership, debt policy, and asset growth on dividend policy. Using descriptive and verification methods, this research focuses on food and beverages sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2021 period. From an initial population of 30 companies, 22 companies were selected as samples through purposive sampling method. The results of the analysis show that managerial ownership, institutional ownership, public ownership, debt policy, and asset growth have a positive and significant effect on dividend policy. These findings reinforce agency and signaling theories, showing how ownership factors and financial policies play a role in influencing corporate dividend decisions